Paraloid® B-72/B-48N 1:1 as an Adhesive for Use in Hot Climates: Literature Review, Laboratory Testing, and Observational Field Study. (18th August 2022) - Davis, Suzanne L.; Roberts, Caroline; Poli, Andrea
ABSTRACT: This paper describes an investigation into 1:1 Paraloid® B-72/B-48N as a conservation adhesive for use in hot climates. The study was driven by archaeological conservation work at El-Kurru, Sudan, a Saharan Desert site where daytime high temperatures can reach 45°C. Paraloid® B-72 is a favorite adhesive for use with archaeological materials for many reasons – notably its stability and long-term reversibility – but its product literature reports a glass transition temperature (Tg) of 40°C. Pottery reconstructed with Paraloid® B-72 slumps within one year at El-Kurru, and joins fail completely after another year. For this reason, we investigated blending Paraloid® B-72 with another thermoplastic acrylic resin, Paraloid® B-48N, which has a reported Tg of 50°C. Research included a literature search to investigate Paraloid® B-48N's long-term stability, reversibility, and the temperature at which it fails. Dynamic mechanical analysis (DMA) was conducted to determine the Tg behavior of Paraloid® B-72, Paraloid® B-48N, and a 1:1 blend of the two resins. Pottery joined with the 1:1 mixture was observed over a four-year period at El-Kurru to evaluate the mixture's performance in a hot archaeological field setting. Although the 1:1 blend performed better than Paraloid® B-72, it was less heat tolerant than expected based on our DMA results as well as literature reports of the performance of similar adhesives. Tg can be defined in multiple ways, and we suggest that the most useful Tg measurement for conservators is the onset temperature at which the glass transition begins. Further, we suggest that creep testing will provide a better indication of the long-term stability of adhesives under mechanical stress, surpassing Tg as a reliable predictor of performance.